Effect of Alpha-Lipoic Acid on the Development, Oxidative Stress, and Cryotolerance of Bovine Embryos Produced In Vitro - Mariana Moreira dos Anjos; Gabriela Rodrigues de Paula; Deborah Nakayama Yokomizo; Camila Bortoliero Costa; Mariana Marques Bertozzi; Waldiceu Aparecido Verri; Amauri Alcindo Alfieri; Fábio Morotti; Marcelo Marcondes Seneda (Veterinary Sciences)
Oxidative stress (OS) induced by an imbalance in reactive oxygen species (ROS) levels in vitro impairs embryonic development. Here, we assessed the effects of alpha-lipoic acid (ALA) in in vitro production media on OS reduction, embryonic development, and cryotolerance of bovine embryos. We evaluated the effects of adding different concentrations of ALA (2.5, 5, 10, and 25 μM) to in vitro maturation (IVM) or in vitro culture (IVC) medium on embryonic development. We also determined the effects of adding ALA (25 μM) to the IVM and IVC medium in the same routine on the development and quality of embryos, ROS levels, and cryotolerance. Embryos were produced in vitro using conventional protocols for each treatment. The inclusion of ALA in the IVM and IVC media did not affect the development or quality of embryos; however, it reduced ROS levels in grade II embryos and increased hatching after 12 h on day 7 in grade I embryos and on day 8 in grade II embryos after warming. These findings prompt questions regarding the potential of ALA in improving embryo metabolism, considering the initial embryo recovery in the first few hours of embryo warming.